The challenges of integrating domestic violence in to court connected ‘Adr’ processes in Nigeria - Umar, Mohammed Amin; Abdul Wahab, Mohd. Iqbal; Mohd Zin, Najibah; Wan Muhammad, Ramizah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Alternative dispute resolution has always been a panacea for access to justice and access to justice is any process or procedure that will make justice accessible, available and affordable. The elitist and technical litigation system has failed to respond with promptitude the societal quest for justice in the dawn of painful injustice. These realities exceedingly justified the establishment of the court connected ‘ADR’ processes in Nigeria. There is a universal consensus that one of the pervasive and endemic threat to global peace and development is domestic violence and has also bedevilled Nigeria and about to be declare a national malaise. This study seek to highlight the extent and severity of domestic violence and the need to be included in to purview of court connected ‘ADR’ system having satisfy the threshold severity of violence emerging from family/marital relationship. This study will also distinguish family/marital disputes from domestic violence and critique the jurisdiction of family court established without regard to the intricate complexities of family disputes and domestic violence. This study found that there is need to reposition the multi-door court house in both conceptual and structural paradigm with a view of integrating heterogeneous Nigeria and plural legal system.